PSYCHOLOGICAL CONSEQUENCES OF CORONAVIRUS: SUGGESTED SOLUTIONS FOR ATHLETES - Leila Heidaryani; Mohsen Keramatimoghadam; Majid Keramatimoghadam (Sport Scientific And Practical Aspects, 2025)
Coronaviruses are a large family of viruses and a subset of coronaviruses that range from the common cold virus to the cause of more serious illnesses such as SARS, Mers, and Covid. So far, however, seven human-transmitted coronaviruses have been discovered, the latest of which, the new coronavirus, spread to humans in December 2019 in Wuhan, China. It is observed that coronavirus disease due to unknown psychological consequences such as anxiety, stress, self-illness, obsessive-compulsive disorder, coronary phobia and finally depression and social isolation, which in addition to physical and physical injuries, causes serious psychological damage. Provided for members of the community; By focusing on the idea of positivity (resilience, hope, optimism, self-efficacy) and strengthening self-management behaviors, as well as managing negative emotions such as fear, stress, anxiety, sadness, anger and depression to strengthen the immune system and We can go to war with the Corona virus and be sure to defeat it. Applying this method (positivity and focusing on good angles) at all levels of prevention and treatment of patients with physical diseases, including coronary heart disease, seems necessary.